2007
DOI: 10.2310/7070.2007.0027
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculose du cavum

Abstract: Nasopharyngeal tuberculosis is increasingly frequent and poses a diagnostic and therapeutic problem. Through a retrospective study spread out over 4 years, we brought back six cases of nasopharyngeal tuberculosis, including two men and four women of an average age of 41 years. The diagnosis was made, for all of our patients, after histologic study when we found typical tuberculosis lesions on biopsy specimens. The diagnosis of tuberculosis was established; all patients had an antituberculosis medical treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Literature was searched from the PubMed database by utilizing the key word “nasopharyngeal tuberculosis.” Between August, 1947, and April, 2015, case reports of NPTB were noted in over 60 cases from both English and non-English articles. Large series studies were frequently reported from Asia ( Table 1 ) [ 9 – 18 ]. There was a slight predominance of woman in all large series studies [ 10 , 11 , 13 – 15 , 18 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Literature was searched from the PubMed database by utilizing the key word “nasopharyngeal tuberculosis.” Between August, 1947, and April, 2015, case reports of NPTB were noted in over 60 cases from both English and non-English articles. Large series studies were frequently reported from Asia ( Table 1 ) [ 9 – 18 ]. There was a slight predominance of woman in all large series studies [ 10 , 11 , 13 – 15 , 18 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Large series studies were frequently reported from Asia ( Table 1 ) [ 9 – 18 ]. There was a slight predominance of woman in all large series studies [ 10 , 11 , 13 – 15 , 18 ]. NPTB commonly occurred in adults with varied average ages in each report.…”
Section: Epidemiologymentioning
confidence: 99%